The impact of quantitative easing on bank loan supply and monetary policy implementation in the euro area - Maximilian Horst; Ulrike Neyer (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
In March 2015, the Eurosystem launched its QE-programme. The asset purchases induced a rapid and strong increase in excess reserves, implying a structural liquidity surplus in the euro area banking sector. Against this background, the first part of this paper analyses the Eurosystem's liquidity management during normal times, crisis times and times of too low in ation. With a focus on the latter, the second part of this paper develops a relatively simple theoretical model in which banks operate under a structural liquidity surplus. The model shows that increasing excess reserves have no or even a contractionary impact on bank loan supply. As the newly created excess reserves are heterogeneously distributed across euro area countries, the impact of QE on bank loan supply may differ across countries. Moreover, we derive implications for monetary policy implementation. Increases in the central bank's main refinancing rate as well as in the minimum reserve ratio and decreases in the central bank's deposit rate develop expansionary effects on loan supply - contrary to the case in which banks face a structural liquidity deficit.
Keywords: E43; E51; E52; E58; G21; 330; monetary policy; quantitative easing (QE); monetary policy implementation; excess liquidity; loan supply; bank lending channel